2012
DOI: 10.4067/s0717-97072012000200020
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Bonded-Phases of Calixarene-Sulfonyl-Carboxamides in Partial-Cone Conformation for Determination of Salbutamol in Livestock by Nano-Mediated Bonded-Phases: Nano-Baskets of Calixarene in Partial-Cone Conformation

Abstract: A new sensitive method for determination of salbutamol, as a nutrient repartitioning agent, in livestock is presented to protect the consumers. Eight nanobaskets of p-tert-calix [4]arene bearing di-[N-(X)sulfonyl carboxamide] and di-(1-propoxy) in partial-cone conformation were synthesized and were used to prepare bended phases of HPLC-UV. The new synthesized bonded-phases were characterized and optimized, the bonding interactions of solute and stationary phases were examined and the main interactions were rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Such observation was noticed previously by Salem et al [52] and agrees with what stated by Mokhtari and Pourabdollah. [53] They found that hydrophobic calixarenes lack solubility in biological media and thus they are unsuitable for biological evaluation as antimicrobial agents, while para-sulfonato-, phosphonato-or other hydrophilic analogues show bioactivity in different biological systems. Moreover, it was reported that peptide-calixarene exhibited moderate to good activity only against Gram positive bacteria with MIC (4-64 µg/ml), [54][55] while tetra-para-guanidinoethyl-calix [4]arene showed antibacterial activity with MIC (2-64 mg/ml).…”
Section: Crystal Structure Of 6•(dmso) 8 Lattice Inclusion Complexmentioning
confidence: 99%
“…Such observation was noticed previously by Salem et al [52] and agrees with what stated by Mokhtari and Pourabdollah. [53] They found that hydrophobic calixarenes lack solubility in biological media and thus they are unsuitable for biological evaluation as antimicrobial agents, while para-sulfonato-, phosphonato-or other hydrophilic analogues show bioactivity in different biological systems. Moreover, it was reported that peptide-calixarene exhibited moderate to good activity only against Gram positive bacteria with MIC (4-64 µg/ml), [54][55] while tetra-para-guanidinoethyl-calix [4]arene showed antibacterial activity with MIC (2-64 mg/ml).…”
Section: Crystal Structure Of 6•(dmso) 8 Lattice Inclusion Complexmentioning
confidence: 99%
“…Initially developed to address respiratory‐related allergy conditions, salbutamol has found applications in a variety of medical contexts 7 . However, SAL is unlawfully applied to animals to boost the formation of muscle tissue 8 . In farm animals, SAL is used at high doses, resulting in a predominant muscle‐to‐fat ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Starting with 1992, the International Olympic Committee included the β2‐agonists in the “banned drugs in sports” list. In order to monitor therapeutic use as well as to control illegal use of β2‐agonists, various analytical methods for the detection of these drugs in biological matrixes have been adopted, including high‐performance liquid chromatography 79, capillary electrophoresis 10, flow‐injection spectrophotometric 11, solid‐phase extraction method 12 and chemiluminescence 13. Although these methods are sensitive, complicated instruments and time‐consuming sample pretreatment restrict their wide application.…”
Section: Introductionmentioning
confidence: 99%